One-Pot Microwave-Assisted Synthesis of Graphene/Layered Double Hydroxide(LDH) Nanohybrids - Lonkar, Sunil P.; Raquez, Jean-Marie; Dubois, Philippe (Nano-micro letters, 2015)
A facile and rapid method to synthesize graphene/layered double hydroxide(LDH)nanohybrids by a microwave technique is demonstrated.The synthesis procedure involves hydrothermal crystallization of Zn–Al LDH at the same time in situ reduction of graphene oxide(GO)to graphene.The microstructure,composition,and morphology of the resulting graphene/LDH nanohybrids were characterized.The results confirmed the formation of nanohybrids and the reduction of graphene oxide.The growth mechanism of LDH and in situ reduction of GO were discussed.The LDH sheet growth was found to prevent the scrolling of graphene layers in resulting hybrids.The electrochemical properties exhibit superior performance for graphene/Zn–Al LDH hybrids over pristine graphene.The present approach may open a strategy in hybridizing graphene with multimetallic nano-oxides and hydroxides using microwave method.